2023
DOI: 10.1002/adfm.202305153
|View full text |Cite
|
Sign up to set email alerts
|

Solvent Exchange Induced In Situ Formed Hydrogel as Liquid Embolic Agents

Abstract: Endovascular embolization can selectively deploy embolic agents into diseased or injured blood vessels to complete the treatment. However, traditional embolic agents still face challenges, such as poor intravascular diffusivity, non‐biodegradable, unstable mechanical properties, radiolucency, and recanalization. Herein,  we report a poly (lipoic acid‐tannic acid)/tromethamine/Galinstan (PLTTG) dimethyl sulfoxide (DMSO) solution‐derived hydrogel liquid embolic agent. By injecting PLTTG DMSO solution into body f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…Especially at 8 weeks, the left kidney atrophy was accompanied by a compensatory increase in the right kidney in the animals, particularly for those dosed by the highconcentration hydrogel, after which the residue weight of the kidney in the embolized side is less than 20 wt % (Figure S10), considered to be a significant shrinkage. 31,59,60 These results demonstrated that the CDN hydrogel remained stable in the left kidney without any migration and fragmentation and indicated that the renal artery and its branches can be effectively embolized without recanalization. Histopathological examination of the kidney resected from the embolized side shows that the renal cortex gradually shrank and thinned after embolization.…”
Section: ■ Results and Discussionmentioning
confidence: 66%
See 3 more Smart Citations
“…Especially at 8 weeks, the left kidney atrophy was accompanied by a compensatory increase in the right kidney in the animals, particularly for those dosed by the highconcentration hydrogel, after which the residue weight of the kidney in the embolized side is less than 20 wt % (Figure S10), considered to be a significant shrinkage. 31,59,60 These results demonstrated that the CDN hydrogel remained stable in the left kidney without any migration and fragmentation and indicated that the renal artery and its branches can be effectively embolized without recanalization. Histopathological examination of the kidney resected from the embolized side shows that the renal cortex gradually shrank and thinned after embolization.…”
Section: ■ Results and Discussionmentioning
confidence: 66%
“…The low-concentration group was dominated by marginal atrophy, and the high-concentration group had a larger range of lesions. Especially at 8 weeks, the left kidney atrophy was accompanied by a compensatory increase in the right kidney in the animals, particularly for those dosed by the high-concentration hydrogel, after which the residue weight of the kidney in the embolized side is less than 20 wt % (Figure S10), considered to be a significant shrinkage. ,, These results demonstrated that the CDN hydrogel remained stable in the left kidney without any migration and fragmentation and indicated that the renal artery and its branches can be effectively embolized without recanalization.…”
Section: Resultsmentioning
confidence: 86%
See 2 more Smart Citations
“…Hydrogels with “liquid–solid” conversion function successfully integrate the advantages of solid and liquid embolic agents and avoid its defects, and have become one of the new hotspots in the treatment of tumors in recent years. Hydrogels are an ideal embolic agent for tumor interventional therapy owing to its adjustable viscosity, mechanical properties, gelation time, injection force and embolic pressure, good biocompatibility and biodegradability, and impermeable X-ray line, as well as excellent embolization performance and intravascular diffusivity [ 35 ]. Generally, hydrogels are polymer materials that are prepared by physical or chemical cross-linking using synthetic or natural polymers, which are extremely hydrophilic gels with three-dimensional network structures [ 36 , 37 ].…”
Section: Introductionmentioning
confidence: 99%